Mining Web and social networks for consumer attitudes towards government-owned Croatian national airline - Jakopović, Hrvoje (Array, 2014)
The paper gives a critical insight into process of evaluation in public relations and also points out similarities and differences among contemporary PR and marketing. The aim was to examine the applicability of sentiment analysis to image measurement in a case of Croatian national airline Croatia Airlines (CA) and evaluate company's public relations efforts. The authors observed Croatia Airlines during the reconstruction phase, after several years which company marked with strikes and financial problems. The analysis showed that company has mostly positive image among customers and in new media. Company's Facebook page was analyzed with a goal to determine PR efforts. Thus, results indicated that the page is mainly used for one-way communication. This showed how efficient public relations were and where the company has place for improvement. The costumer opinions and attitudes were revealed as very valuable information for company's strategic approach in building its image.